The power of character in leadership - Munroe, Myles (New Kensington, PA : Whitaker House, 2014)
"Explores the crisis of character in leadership, how beliefs shape values and morals, the process of character development, essential qualities of principled leaders, how to recover after moral failure, and how to ensure leadership influence is both effective and enduring"-- Provided by publisher.
Includes bibliographical references (230-237).
Keywords: Leadership -- Moral and ethical aspects